Financial Inclusion Strategy To Increase The Welfare Of Regional Community Industry In Gresik Regency Of East Java - Ratnawati, Tri; Mujanah, Siti; Lokajaya, Nyoman (Archives of Business Research, 2018)
The problems that occurred in the tourism area of small and medium industry community of Giri Gresik Regency based on survey results of businessmen still do not understand financial inclusion so they still do not have bank account. the purpose of this study is to test and analyze financial inclusion indicators. Research method using quantitative method with partial least square analysis technique. Based on the analysis of financial inclusion factors, attributes that significantly affect small and medium industries are credit management, knowledge of credit guidelines, consumer over in-debtedness, savings and deposit functions. The strategy that must be done in the short term based on attributes in this research is to provide financial inclusion education with attention to significant attributes. provide assistance from financial planning to the preparation of financial statements. provide the motivation to separate between family finance and business finance. While long-term strategy that together with tourism aspect is expected to become industrial tourism industry that require production of small and medium industries based on economic potential, especially in agriculture, processing industry, and tourism, and trade. In addition, it needs to be improved facilities and infrastructure that support tourism such as hotels and restaurants.